Association of critically short telomeres with brain and blood markers of ageing and Alzheimer’s disease in older adults - Asrar Lehodey; Perla Kaliman; Cassandre Palix; Robin de Florès; Edelweiss Touron; Anne-Laure Turpin; Séverine Fauvel; Florence Mézenge; Brigitte Landeau; Anne Chocat; Agathe Vrillon; Claire Paquet; et al. (Alzheimer’s Research & Therapy)
Abstract Background Accumulation of critically short telomeres (CST) is implicated in decreased tissular regenerative capacity and increased susceptibility to degenerative diseases such as Alzheimer’s disease (AD). Telomere shortening has also been associated with age-related brain changes. However, it remains unclear whether CST accumulation is directly associated with AD markers or instead amplifies age-related effects, potentially increasing susceptibility of developing AD in cognitively healthy older adults. Methods This cross-sectional study used baseline data of 129 community-dwelling cognitively healthy older adults from the Age-Well trial (NCT02977819), aged 65 years and older enrolled between 2016 and 2018, in France. Using linear regressions, we analyzed the relationship between an innovative marker of telomere shortening, the percentage of CST (%CST), structural, functional and molecular neuroimaging outcomes, and multiple blood-based biomarkers related to AD pathophysiology. The effect of apolipoprotein E ε4 genotype (APOE4) was assessed on these relationships using interaction analysis. Results A higher %CST was associated with lower global kurtosis fractional anisotropy (β = -.230; P = .010), particularly in frontal and temporal regions. A higher %CST was also related to higher plasma levels of Neurofilament light chain (β = .195; P = .020) and a lower subiculum volume (β = -.206; P = .020), although these associations did not meet the threshold for multiple comparisons. %CST was not associated with AD-related neuroimaging markers, including the AD-sensitive gray matter pattern (β = -.060; P = .441), glucose metabolism pattern (β = -.099; P = .372), brain perfusion pattern (β = -.106; P = .694) or hippocampus volume (β = -.106; P = .194). In APOE4 carriers, higher %CST was associated with lower subiculum (β = -.423; P = 0.003), DG (β = -.410; P = 0.018) and CA1 volumes (β = -.373; P = 0.024), even though associations with DG and CA1 volumes did not survive multiple comparison. Conclusions Although an increase in %CST does not appear to be directly linked to the pathophysiology of AD in cognitively healthy older adults, it could heighten the susceptibility of APOE4 carriers to develop AD plausibly due to greater vulnerability to age-related effects. However, longitudinal studies would be necessary to determine whether %CST influences the development and progression of AD later in life.